Development Plan for Enhancing PT XYZ Corporate University - Kartika Chandra Dewi; Wendra Wendra (Universitas Muhammadiyah Palembang, 2025)
The corporate university serves as a strategic solution for companies seeking to implement structured learning programs aligned with their business strategies. The purpose of this study is to assess the readiness level of the corporate university at PT XYZ and to develop an improvement plan to address existing gaps. This research adopted a qualitative approach, utilizing observation and in-depth interviews with internal stakeholders directly involved in the transformation of the conventional training unit into a corporate university. Data analysis methods included observational checklist analysis, data reduction from interview transcripts, keyword identification, coding, and drawing conclusions based on the data. The findings reveal that out of twenty-six identified corporate university functions and activities, four have not yet been fulfilled by PT XYZ’s corporate university. These unmet areas broadly relate to the corporate university’s roles in employee career planning, strategic recruitment, succession planning, and the provision of library and electronic information resources. Based on these findings, this study proposes a development plan to enhance the corporate university at PT XYZ.